Teachers and Students’ Perception on Blended Learning on Covid -19 Epidemic Situation - Shahana K. (Integrated Journal for Research in Arts and Humanities, 2022)
This paper's purpose is to discover how tutors and pupils feel about the adoption of a blended way of learning in the English language in the higher education system in Kollam, Kerala. The research approach used in this study is a hybrid of qualitative and quantitative methods. Teachers and students were chosen at random from nine senior high schools in Kollam to participate. The procedure and data recurring are to be carried out by providing a structured questionnaire to every one of the members, which covered seven components of how they responded to the benefits for English blended method of learning for both tutors and pupils. Regarding the collection of data, an analysis was conducted based on the perceptions of teachers and students. According to the teachers, the greatest benefit was that it was difficult for them to prepare data and use the electronic media. For the present, pupils said that the primary benefit was that English blended learning may help them enhance their language skills (69 percent acumen regarding response). Blended learning must continue during this period of Covid 19, according to proposals.